EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DAN THREE STEPS INTERVIEW (TSI) PADA MATERI FUNGSI DITINJAU DARI KECERDASAN LOGIS MATEMATIS - Riyanto, Nandyar Fisthi; Mardiyana, Mardiyana; Subanti, Sri (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract:The purpose of this study was to determine the effect of the learning models TAI, TSI, and direct learning model on mathematics learning achievement viewed from the students logical mathematical intelligence. The type of this study was quasi experimental study with 3x3 factorial design. The population were the eighth-grade students of junior high schools in Boyolali Regency in the academic year of 2015/2016. Instruments used for data collection were mathematics achievement test and logical mathematical intelligence test. The data analysis technique used was the two-way ANAVA with unequal cell. Based on the hipothesis test, they were concluded that: (1) The mathematics learning achievement of TAI was better than TSI and direct learning model, the mathematics learning achievement of TSI was better than direct learning model. (2) The mathematics learning achievement of students with high logical mathematical intelligence were better than average and low logical mathematical intelligences. Students with average logical mathematical intelligence were better than low logical mathematical intelligences. (3) Students with high logical mathematical intelligence who were treated by TAI, TSI, and direct learning models had same mathematics learningÂ achievement; students with average logical mathematical intelligence who were treated by TAI was same of TSI and was better than direct learning model, TSI was better than direct learning model; students with low logical mathematical intelligence who were treated by TAI had better mathematics learning achievement than TSI and direct learning model, TSI students were better than direct learning model model. (4) In TAI learning model, the mathematics learningÂ achievement of high logical mathematical intelligence were better than the average and lower logical mathematical intelligence, the mathematics learning achievementof average has equal with low logical mathematical intelligence; in TSI learning model, students with high logical mathematical intelligence has equal of average logical mathematical intelligence, the mathematics learning achievements of high and average logical mathematical intelligence were better than the low logical mathematical intelligence; in direct learning model, students with high logical mathematical intelligence has better mathematics learning achievement than high and average of logical mathematical intelligence,Â students with average logical mathematical intelligence has better mathematics learning achievement than low of logical mathematical intelligence.Keywords:Team Assisted Individualization, Three Steps Interview, Direct Learning Model, Logical Mathematical Intelligence, Achievement.